Zur Psychidenfauna Albaniens unter Berücksichtigung der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes (Lepidoptera: Psychidae). - Weidlich, Michael (Contributions to Entomology = Beiträge zur Entomologie, 2013)
In the present paper an overview of the albanian Psychid-fauna is given and evaluated the relevant literature. The first records date from the early years of the 20th Century and a summary of the species inventory was given in 1931. The expedition of the German Entomological Institute in Eberswalde to Albania in 1961 provided further evidence. Since 2006, the author was several times in Albania for studies of Psychid-fauna. The records of Psychids are currently a total of 77 localities in 24 provinces spread over the entire country. Until 1931 and supplemented by the Albania Expedition 1961 a total of 16 species were known. The author found for the first time five species for the albanian faune. In addition to the initial description of Epichnopterix hellenidensis are Pseudobankesia sp., Luffia lapidella (Goeze, 1783), Stichobasis helicinoides (Heylaerts, 1879) and Oiketicoides lutea (Staudinger, 1871). Until today 21 Psychid-species have been detected. Taleporia politella (Ochsenheimer, 1816) and Acanthopsyche zelleri (Mann, 1855) must be delete from the faunistical list from zoogeographical aspect, other taxa are discussed. The current literature of Albania for Proutia betulina (Zeller, 1839), Psyche casta (Pallas, 1767) and Sterrhopterix fusca (Haworth, 1809) need to be revised, since they come from sites that are currently among the neighboring Kosovo and Macedonia. In addition, an overview of all Albanian species to occuring in the neighboring countries is given.KeywordsAlbania, faunistic review, Psychidae, Lepidoptera